HISTOPATHOLOGICAL CHANGES IN THE LUNGS OF WHITE RATS POST ADMINISTRATION OF MIMOSINE FROM LEUCAENA LEAF SIMPLICIA - Gheasella Fia Gunawan; I Ketut Berata; Hamong Suharsono; Ni Luh Eka Setiasih; I Made Merdana; I Wayan Sudira (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Lamtoro leaves (Leucaena leucochepala) are widely used as forage for cattle because they contain high protein, flavonoids, tannins and other useful nutrients. Apart from containing useful nutrients, it turns out that lamtoro leaves contain a toxic ingredient, namely mimosine, which can cause alopecia and reproductive disorders. This study aims to determine the histopathological changes in the lungs of white rats (Rattus norvegicus) after administration of mimosine from lamtoro leaf simplicia. The study used 20 rats divided into 4 treatment groups, namely P0 (negative control), P1 (positive control) which were given standard mimosine produced by Sigma 5 mg/head/day, P2 (treatment given mimosine from lamtoro leaf simplicia dose of 50 mg/day). head/day, and P3 (treatment given mimosine from lamtoro leaf simplicia dose of 150 mg/head/day. The treatment was given orally for 14 days. On the 15th day all experimental animals were sacrificed to have their lung tissue taken. Then preparations were made histopathology using the hematoxylin eosin (HE) staining method. Examination of histopathological changes including congestion, bleeding and inflammation was carried out using scoring to categorize mild, moderate and severe lesions. The results of the examination in the form of scoring data were analyzed using the Kruskall Wallis and Mann Whitney tests.The results showed that there were significant differences (P<0.05) in lesion congestion, bleeding and inflammation compared to controls. There was a significant difference (P<0.05) between treatments P2 (150mg/head/day) and P3 (50mg/head/day) based on inflammatory lesions, but not significant (P>0.05) on coagulation and bleeding lesions. The conclusion is that administration of mimosine from lamtoro leaf simplicia can cause histopathological lesions of congestion, bleeding and inflammation in the lungs of white rats. The difference in dose of mimosine from lamtoro leaf simplicia between 50mg/head/day and 150mg/head/day only differs in inflammatory lesions, but not in congestion and bleeding lesions. The suggestion is that this research can become a basic reference and that there be futher research regarding dose compared to control.